Pengaruh Human Capital dan Corporate Philanthropy Terhadap Kinerja Keuangan - Declyanda Mahardika, Gita; Sulistyowati, Erna (Forum Kerjasama Pendidikan Tinggi, 2025)
This study is motivated by the essential roles of human capital and corporate philanthropy in enhancing company performance, particularly in the banking sector. Human capital is considered an intangible asset that contributes to efficiency and productivity, while corporate philanthropy is believed to strengthen corporate reputation and public trust. However, previous studies have shown mixed findings regarding the influence of these two variables on financial performance, indicating the need for further investigation. This research aims to examine the effect of human capital and corporate philanthropy on financial performance in conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Human capital is measured using Value Added Human Capital (VAHU), corporate philanthropy is assessed through the Corporate Social Responsibility Disclosure Index (CSRDI), and financial performance is proxied by Return on Assets (ROA). The study employs a quantitative approach using multiple linear regression analysis and includes 34 companies as samples, with a total of 102 observations. The results show that human capital has no significant effect on financial performance (p-value = 0.243), and corporate philanthropy also has no significant effect on financial performance (p-value = 0.319). These findings indicate that investment in human resources and philanthropic activities does not necessarily have a direct impact on the profitability of banking companies in Indonesia.